Comparing the Cost-Effectiveness of Campaigns Delivered via Various Combinations of Television and Online Media - Vanessa Allom; Vanessa Allom; Michelle Jongenelis; Terry Slevin; Terry Slevin; Stacey Keightley; Fiona Phillips; Sarah Beasley; Simone Pettigrew (Frontiers Media S.A., 2018)
BackgroundReflecting the increasing prevalence of online media, many mass media health campaigns are now delivered using both television (TV) and online media formats. The aim of this study was to evaluate a smoking cessation mass media campaign according to the cost-effectiveness of the various combinations of TV and online media formats to inform future media buying decisions.MethodsA quasi-experimental interrupted time series approach was employed. The campaign was delivered in seven 1-week bursts using TV, online video (OV), or online display (OD) (e.g., banner ads) formats in isolation and in various combinations over a 13-week period. Campaign bursts were separated by "off-weeks" in which no campaign materials were delivered. Assessed outcomes were the number of campaign response "events" recorded (campaign web page views, calls to a smoking cessation telephone service, and registrations for smoking cessation services). The cost-effectiveness of each individual and combined media format condition in terms of these outcome variables was calculated using attributed production and broadcasting costs.ResultsOverall, OD alone was found to be the most cost-effective means of achieving the nominated campaign outcomes, followed by a combination of OV and OD and a combination of TV and OV. The use of TV in isolation was the least cost-effective.ConclusionThe results of this evaluation indicate that online media constitute a promising means of enhancing the cost-effectiveness of smoking cessation campaigns. Future research assessing a broader range of outcomes, especially smoking cessation, is needed to provide a more comprehensive account of the cost-effectiveness of various campaign media.